2020
DOI: 10.1101/2020.05.10.20096925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-White Ethnicity, Male Sex, and Higher Body Mass Index, but Not Medications Acting on the Renin-Angiotensin System Are Associated With Coronavirus Disease 2019 (Covid-19) Hospitalisation: Review of the First 669 Cases From the Uk Biobank

Abstract: Background: Cardiometabolic morbidity and medications, specifically Angiotensin ConvertingEnzyme inhibitors (ACEi) and Angiotensin Receptor Blockers (ARBs), have been linked with adverse outcomes from coronavirus disease 2019 . This study aims to investigate factors associated with COVID-19 positivity for the first 669 UK Biobank participants; compared with individuals who tested negative, and with the untested, presumed negative, rest of the population. Methods:We studied 1,474 participants from the UK Bioban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
(36 reference statements)
2
24
0
Order By: Relevance
“…These patterns are echoed across Europe, with Nordic countries reporting as much as 10× greater risk of COVID-19 in Somali populations 21 . We had previously documented this preponderance of cases amongst BAME individuals in our analysis of the initial UKB data release 16 ; here, we have confirmed the observation in this larger dataset, and importantly demonstrated a non-uniform impact across different BAME groups with highest rates amongst Black followed by Asian ethnicities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These patterns are echoed across Europe, with Nordic countries reporting as much as 10× greater risk of COVID-19 in Somali populations 21 . We had previously documented this preponderance of cases amongst BAME individuals in our analysis of the initial UKB data release 16 ; here, we have confirmed the observation in this larger dataset, and importantly demonstrated a non-uniform impact across different BAME groups with highest rates amongst Black followed by Asian ethnicities.…”
Section: Discussionsupporting
confidence: 87%
“…UKB participants were grouped according to COVID-19 status: test positive, test negative and untested. In the analysis of an earlier data release, we demonstrated similar associations when comparing the untested cohort with both the test negatives and test positives, suggesting that comparison with the whole cohort reveals associations with general hospitalization rather than specifically with COVID-19 16 . Therefore, to avoid bias relating to hospitalization, in the present study, we limited to modelling within the tested cohort.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…Among patients with symptoms, those with severe or critical conditions had much higher BMIs and individuals with obesity prevalence than the normal population or patients who were COVID‐19 negative 32,61–70 . Two studies showed that the odds of having COVID‐19 increased by 30% (OR = 1.30; 95% CI, 1.09–1.54; p = 0.0030) 61 and by 38% (OR = 1.38; p < 0.0001), 32 respectively, among the individuals with obesity (Table 1).…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…Nine studies were conducted in Europe (UK, Italy, France, Spain, Belgium) [18][19][20][21][22][23][24][25][26], 7 studies took place in North America (the USA) [27][28][29][30][31][32][33], while 9 studies were conducted in Asia, mainly in China [31,[34][35][36][37][38][39][40][41]. Finally, we initially included in our quantitative synthesis a study utilizing data from an observational database from 169 hospitals in Asia, Europe, and North America, which was recently retracted and thus excluded from our analysis [42].…”
Section: Resultsmentioning
confidence: 99%